2020
DOI: 10.1111/cts.12892
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling of Intra‐Tumor Spatial Distribution of Antibody‐Drug Conjugates: Insights into Dosing Strategies in Oncology

Abstract: Antibody drug conjugates (ADCs) provide targeted delivery of cytotoxic agents directly inside tumor cells. However, many ADCs targeting solid tumors have exhibited limited clinical efficacy, in part, due to insufficient penetration within tumors. To better understand the relationship between ADC tumor penetration and efficacy, previously applied Krogh cylinder models that explore tumor growth dynamics following ADC administration in preclinical species were expanded to a clinical framework by integrating clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The safety profile of sacituzumab govitecan in this phase 2 trial was consistent with that previously reported in the phase 1 trial (NCT01631552) and phase 1/2 trial (NCT01631552) of this agent in other metastatic solid tumours [16,22]. The most common adverse events (AEs) of any grade were nausea (80%), diarrhoea (61%), fatigue (46%), alopecia (39%), and neutropenia (37%) [16].…”
Section: Safetysupporting
confidence: 83%
“…The safety profile of sacituzumab govitecan in this phase 2 trial was consistent with that previously reported in the phase 1 trial (NCT01631552) and phase 1/2 trial (NCT01631552) of this agent in other metastatic solid tumours [16,22]. The most common adverse events (AEs) of any grade were nausea (80%), diarrhoea (61%), fatigue (46%), alopecia (39%), and neutropenia (37%) [16].…”
Section: Safetysupporting
confidence: 83%
“…PBPK is widely used for the characterization of PK and drug-drug interaction studies for small and large molecules. PBPK models have been developed for several ADCs [85][86][87][88]. Considering the complexities of an ADC molecule, the predictive power of PBPK models requires extensive validation from external data (observed data) before its use can be justified for ADCs.…”
Section: Physiologically Based Pharmacokinetic Models (Pbpk)mentioning
confidence: 99%
“…Considering the complexities of an ADC molecule, the predictive power of PBPK models requires extensive validation from external data (observed data) before its use can be justified for ADCs. It is also important to establish if a whole body or minimal PBPK [88] model is needed for ADCs. In short, modeling and simulation is a helpful tool to obtain relevant information regarding ADCs before clinical trials are initiated.…”
Section: Physiologically Based Pharmacokinetic Models (Pbpk)mentioning
confidence: 99%
“…[23] ADCs (Tables S1 and S2, Supporting Information), have demonstrated rapid growth in recent decades for treating a variety of cancers, with 5 ADCs alone approved over the past 2 years. Despite these successes, several limitations have persisted, [24] including off-target toxicity, drug resistance, relatively low drugantibody ratios, and poor solid tumor penetration, [25,26] that, in turn, may reduce efficacy. [25] As a result, several ADCs used in the clinic have been discontinued.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these successes, several limitations have persisted, [24] including off-target toxicity, drug resistance, relatively low drugantibody ratios, and poor solid tumor penetration, [25,26] that, in turn, may reduce efficacy. [25] As a result, several ADCs used in the clinic have been discontinued. Such developments have spurred explosive growth over the past decade in a diverse array of alternative targeted nanodelivery vehicles used as monotherapies or as part of combinatorial regimens [27] for treating AGC; these have been summarized in a number of excellent comprehensive reviews.…”
Section: Introductionmentioning
confidence: 99%